2016
DOI: 10.1063/1.4967880
|View full text |Cite
|
Sign up to set email alerts
|

How plasma induced oxidation, oxygenation, and de-oxygenation influences viability of skin cells

Abstract: The effect of oxidation, oxygenation, and de-oxygenation arising from He gas jet and He plasma jet treatments on the viability of skin cells cultured in vitro has been investigated. He gas jet treatment de-oxygenated cell culture medium in a process referred to as “sparging.” He plasma jet treatments oxidized, as well as oxygenated or de-oxygenated cell culture medium depending on the dissolved oxygen concentration at the time of treatment. He gas and plasma jets were shown to have beneficial or deleterious ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 59 publications
3
25
1
Order By: Relevance
“…chronic wounds and cancers. It has been shown through in vitro cell studies and in vivo animal experiments that cold atmospheric plasma, herein referred to as plasma, might accelerate wound healing by stimulation of cell growth and migration [1][2][3][4][5][6][7][8][9][10][11], and also decontaminate infected wounds through targeted destruction of bacterial cells [12][13][14][15][16][17][18][19][20][21][22]. Similar results have been obtained in clinical studies where the efficacy of plasma in wound decontamination and healing has been demonstrated [23][24][25][26].…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…chronic wounds and cancers. It has been shown through in vitro cell studies and in vivo animal experiments that cold atmospheric plasma, herein referred to as plasma, might accelerate wound healing by stimulation of cell growth and migration [1][2][3][4][5][6][7][8][9][10][11], and also decontaminate infected wounds through targeted destruction of bacterial cells [12][13][14][15][16][17][18][19][20][21][22]. Similar results have been obtained in clinical studies where the efficacy of plasma in wound decontamination and healing has been demonstrated [23][24][25][26].…”
Section: Introductionsupporting
confidence: 55%
“…The cell stimulatory effect of plasma has also been explained by the plasma delivery of RONS to tissue fluid, tissue and cells [6,7]. Generally, if the dose or rate of delivery (flux) of RONS is kept low enough it is argued that RONS enhance cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent positive peaks (above 0) were fitted for H 2 O 2 , NO 2 − , and NO 3 − , and were attributed to the plasma jets generating these molecules in the DI water. Negative peaks were fitted for O 2 , and were attributed to a decrease of the O 2 concentration in the DI water caused by the He gas flow from the plasma jets purging O 2 out of the DI water [34,38]. From the curve fitting results, we determined that the He plasma jet mainly produced H 2 O 2 in the range of 48.9-55. and 45 µs for the positive polarity plasma jet; whereas, for the negative polarity plasma jet, it increased from 1.5 to 10 µs and then remained relatively constant between 10 and 45 µs.…”
Section: Uv Absorption Spectroscopymentioning
confidence: 98%
“…A subsequent development to the approach described above used gelatin and agarose model targets with either embedded chemical reporters, or simply as films through which plasma-generated RONS traverse, to measure RONS speciation and delivery into and through tissues [36,37,48,[51][52][53][54]. In the latter case, UV-Vis spectroscopy was used to identify RONS that traverse the targets.…”
Section: Delivery Of Rons Into Tissue Modelsmentioning
confidence: 99%